PENGEMBANGAN MANAJEMEN DATA DAN INFORMASI MENGGUNAKAN ANALISIS SOFT SYSTEM METHODOLOGY DI UNIVERSITAS ADVENT INDONESIA - Thalia Dorkas Septiana; Raymond Maulany (TeIKa, 2021)
Education and information are closely related. In the world of education, the operations also require assistance from information systems, for example in managing good and correct data management. Data and information management is an important part of educational institutions such as campuses or universities. Soft system methodology is considered as the most appropriate methodology in data management operations at Advent Indonesia University. Soft system methodology is a system methodology that is used with the intention of explaining the goals of an institution and designing a system or activity to achieve common goals. This study aims to explain and explain how the development of data and information management using soft system methodology analysis. This research is quantitative descriptive, which is a method that describes the results of research in numerical form on an object or variable. Based on the results of this study, it can be concluded that the soft system methodology has a big influence and makes data management more structured at Advent Indonesia University.